Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan dan Kepemilikan Institusional Terhadap Financial Distress - Dita Puspitawati; Rinny Meidiyustiani; Indah Rahayu Lestari (International Forum of Researchers and Lecturers, 2023)
: Financial distress is a condition where a company experiences a decline in financial condition which is usually temporary, but will develop worse if the condition is not quickly overcome and can cause the company to go bankrupt. The purpose of this study is to determine the effect of profitability, liquidity, company size and institutional ownership on financial distress. The population is property and real estate companies listed on the Indonesia Stock Exchange (IDX) in the financial statements for the 2016-2021 period. Samples were determined by purposive sampling techniques with certain criteria and obtained samples of 36 companies. This study used a multiple linear regression analysis method assisted by the SPSS Version 22 program. The results of this study show that profitability as measured by return on equity has a positive and significant effect on financial distress, liquidity as measured by curre ratio has a positive and significant effect on financial distress, while company size does not affect financial distress, institutional ownership positively affects financial distress